Market timing, maturity mismatch, and risk management: Evidence from the banking industry - Benedikt Ruprecht; Oliver Entrop; Thomas Kick; Marco Wilkens (Deutsche Bundesbank, 2013)
We investigate financial intermediaries' interest rate risk management as the simultaneous decision of on-balance-sheet exposure and interest rate swap use. Our findings show that both decisions are substitute risk management strategies. A higher likelihood of bank distress makes banks reduce their on-balance sheet interest rate exposure and simultaneously intensify their swap use. Exogeneity tests indicate that both decisions are only endogenous to each other for banks that start using swaps for the first time. For other banks, the maturity gap is endogenous to the decision to use swaps, but the reverse relationship is exogenous. For banks with trading activity, both decisions are exogenous to each other. We interpret these findings as the maturity gap being largely determined by customer liquidity needs, whereas the decision to use swaps relies on compliance with the interest rate risk regulation. Although hedging motives dominate, we find selective hedging behavior in swap use driven by the slope of the yield curve as well as by funding uncertainty.
Keywords: G21; G32; G33; 330; Duration gap; Interest rate swaps; Selective hedging